Effects of sowing time on growth and yield performance of six high yielding varieties of wheat (Triticum aestivum L.) (Bangladesh Journal of Botany, 2019)
A field experiment was conducted to evaluate the growth and yield performance of six high yielding varieties of wheat viz., BARI Gom-23, BARI Gom-24, BARI Gom-25, BARI Gom-26, BARI Gom-27 and BARI Gom-28 in four sowing time. BARI Gom-24 sown on November 29 produced tallest plant after the age of 45 days with significant variations. Results also indicated that November 15 sown BARI Gom-25 resulted the highest number of tillers, leaves and total dry matter per plant throughout the growth ages with a few exceptions where dry matter produced at the age of 60, 75 and 90 days were significantly higher. Yield parameters viz., number of grains per plant, dry weight of spike, 1000-grain weight, yield per plant, yield per hectare and harvest index were recorded maximum from BARI Gom-25. On the other hand, seeds sown on November 15 produced significantly higher value in all yield contributing characters except number of effective tillers and number of grains per spike. In case of combined treatments, November 15 sown wheat showed similar trend in majority of yield parameters of BARI Gom-25 where, dry weight of spike, 1000- grain weight, yield per plant and yield per hectare were significantly higher than rest of the treatments. Out of six varieties, BARI Gom-25 was the best performed variety. November 15 sown wheat had remarkable effects on yield attributes and yield of most of the varieties but beyond this time yield of wheat reduced significantly.